2022
DOI: 10.5588/ijtld.21.0351
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of treatment outcomes in patients with multidrug-resistant TB

Abstract: BACKGROUND: Treating multidrug-resistant TB (MDR-TB) remains challenging. However, the determinants and timing of poor outcomes during MDR-TB treatment are still poorly understood.METHODS: We conducted a retrospective cohort study on all adult MDR-TB patients treated at Persahabatan Hospital, Jakarta, Indonesia, between January 2013 and December 2016. Risk factors for poor outcomes were analysed using Cox regression.RESULTS: Death occurred at a median time of 6 months (IQR 4–14) and loss to follow-up (LTFU) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…While age 44 years or over (15.7%), HIV positive status (14.7%), earning some income (24.7%), and being on long regimen at the end of treatment (14.3%) were associated with increased odds of dying from DR-TB, in the adjusted regression, only HIV and earning some income signi cantly predicted DR-TB fatality. These nding are similar to those reported in another study where advancing age, HIV infection and diabetes mellitus were associated with poor outcomes and death (27). The WHO also reported that T2DM, HIV, undernutrition, advancing age (> 45 years) and the effects of alcohol abuse were associated with poor outcomes (1) and may re ect immune dysfunction among patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While age 44 years or over (15.7%), HIV positive status (14.7%), earning some income (24.7%), and being on long regimen at the end of treatment (14.3%) were associated with increased odds of dying from DR-TB, in the adjusted regression, only HIV and earning some income signi cantly predicted DR-TB fatality. These nding are similar to those reported in another study where advancing age, HIV infection and diabetes mellitus were associated with poor outcomes and death (27). The WHO also reported that T2DM, HIV, undernutrition, advancing age (> 45 years) and the effects of alcohol abuse were associated with poor outcomes (1) and may re ect immune dysfunction among patients.…”
Section: Discussionsupporting
confidence: 87%
“…Research conducted in Tanzania, Indonesia and elsewhere have reported similar ndings. In terms of time-to-event for poor treatment outcomes among DR-TB patients, Silva et al (37) found that advanced age (> 45 years), DM and HIV were independently associated with poor outcomes within seven months of treatment, while low BMI (< 18kg/m 2 ) and history of LTFU predicted poor outcomes after seven months of treatment (27,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to ndings from a systematic review and meta-analysis on treatment outcomes for DR-TB patients on a communitybased model of careof studies on found that age was not a signi cant contributor to treatment outcomes irrespective of the model of care (20). However, in some instances, advanced age has been found to be signi cantly associated with unfavorable outcomes among MDR-TB (32)(33)(34). The ndings in our study could be explained by the fact that the majority (78.9%) of the study participants were less than 45 years of age.…”
Section: Discussionsupporting
confidence: 85%
“…All subjects were given antiviral therapy either remdesivir, favipiravir, or oseltamivir based on clinical judgement and according to Indonesia National Guideline of Covid-19. 24 One patient was given oseltamivir because remdesivir or favipiravir was contraindicated (GFR <30 ml/min/1,73 m 2 ), and one patient was not in either antiviral because both remdesivir and favipiravir were contraindicated and oseltamivir was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Severe cases was defined as patient with clinical signs and symptoms of pneumonia, and one of the following: 1) respiratory rate > 30 times per minute, 2) signs of respiratory distress, or SpO 2 < 93% with room air. 23,24 Patients included in this study were patients who initially classified as moderate or severe disease. Patients were then observed up to day 14th or concluded earlier if the patients improved and discharged earlier, or worsened and passed away before day 14th.…”
Section: Assessment Patients' Severitymentioning
confidence: 99%